Genetic variability studies among thirty three vegetable soybean genotypes under Manipur condition: Genetic variability studies among thirty three vegetable soybean genotypes under Manipur condition - H NANITA DEVI; D DEVI SR; T H RENUKA DEVI; NILIMA KARAM; T SUNANDA DEVI; L SOPHIA DEVI (Journal of Oilseeds Research, 2023)
The present study was carried out at Central Agricultural University Research Farm, Andro, Imphal East, Manipur, during kharif 2021 to estimate genetic variability parameters of thirty three vegetable soybean genotypes for ten characters. Statistical analysis showed significant differences between the tested genotypes. Maximum phenotypic coefficient of variation value (66.54) and genotypic coefficient of variation value (66.53) was recorded for character fresh pod yield/plant. Heritability (in broad sense) value ranged from 99.99 to 86.53. The estimates of genetic advance expressed as percentage ranged from 137.24 to 118.09. Highest GA over its mean was recorded for fresh pod yield/plant (137.24), followed by number of pods/plant (118.09). The correlation study showed a positive and significant correlation between fresh pod yield/plant and the number of pods/plant, 100 fresh pod weight and 100 fresh seed weight.